EFEK TAMPILAN VISUAL SEDUKTIF DESAIN PESAN MULTIMEDIA TERHADAP KEMAMPUAN TRANSFER - Pranata, Moeljadi (Institute of Research and Community Outreach - Petra Christian University, 2005)
This experiment includes two groups of college students with difference in literacy orientation type%2C visual and verbal%2C all consist of 80 people. The experiment was held to compare impacts of presenting information in essential message design format (DPE) and seductive-visual (DPS). To analyze the experiment%2C MANOVA statistical technique is used with 0.05 in significance level. Groups of students related with different types of message design showed significance dissimilarity in mean result for retention and transfer.The result of Pillais Trace is F=5.941%2C Wilks Lambdas F=5.941%2C Hotellings Traces F=5.941%2C Roys Largest Root F=5.941. Collective manner result showed p=0.000 (p